Macronutrient Iintake and Body Mass Index as Determinants of VO2 Max in Football Athletes at BBC Batuang Taba, Padang City - Dewi, Ghinna Alfitri; Kasmiyetti, Kasmiyetti; Hasneli, Hasneli; Dwiyanti, Defriani; Yuniritha, Eva (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
Maximal oxygen uptake (VO₂ Max) is a key indicator of physical fitness in football athletes, reflecting the body's ability to uptake, transport, and utilize oxygen during intense physical activity. Nutritional factors, particularly macronutrient intake (carbohydrates, proteins, and fats), as well as body mass index (BMI), may influence aerobic endurance. This study aimed to determine the association between macronutrient intake, BMI, and VO₂ Max among football athletes at BBC Batuang Taba Football School, Padang City. A quantitative study with a cross-sectional design was conducted involving 35 athletes selected through purposive sampling. Macronutrient intake was assessed using a 3×24-hour dietary recall, BMI was determined through anthropometric measurements, and VO₂ Max was measured using the beep test. Macronutrient adequacy was evaluated based on the nutritional recommendations of the International Society of Sports Nutrition (ISSN). Data were analyzed using the Chi-square test. The results showed that 65.7% and 57.1% of the athletes had adequate protein and fat intake, respectively, whereas all participants (100%) had inadequate carbohydrate intake. In addition, 57.1% had abnormal BMI, and 51.4% had low VO₂ Max. Chi-square analysis revealed no significant association between macronutrient intake, BMI, and VO₂ Max (p=1.000). Nevertheless, descriptive findings indicated that athletes with adequate protein and fat intake and a normal BMI tended to have better VO₂ Max values. Although no statistically significant associations were identified, adequate nutrient intake and normal nutritional status remain important for maintaining physical fitness and optimizing athletic performance. Regular nutritional assessment and nutrition education are therefore recommended to support the fitness and endurance of football athletes.